Breastfeeding flashcards (BFC): An innovative tool for breastfeeding education using ADDIE model - Rosyidah, Hanifatur; Prameswari Rahayu, Indira; Aisyaroh, Noveri; Mathurin, Jeffthanie (Journal of Health Technology Assessment in Midwifery, 2025)
This study outlines the development and evaluation of Breastfeeding Flashcards (BFC) as a tool to support breastfeeding education for pregnant and postpartum mothers. The flashcards are intended for use by midwives, healthcare professionals, and community health workers or cadres. The development process followed the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The BFC development process involved information gathering, storyboard creation, color coding, and card printing. The content and design were validated through consultations with breastfeeding and media experts. The flashcards were then pre-tested with mothers and community health cadres to assess their usability and effectiveness. Post-implementation surveys and interviews revealed significant improvements in cadres’ knowledge, as confirmed by the Wilcoxon signed-rank test. Cadres were able to effectively deliver breastfeeding education using BFC. Feedback from mothers, cadres, and midwives was highly positive. Cadres found the flashcards easy to use, citing the clear information, supportive images, and brief explanations on the back as helpful for communication. They expressed strong willingness to continue using the tool. Mothers appreciated the support from cadres and found the education beneficial. Overall, BFC proved to be an effective tool in supporting cadres’ breastfeeding education efforts. The involvement of trained cadres in delivering breastfeeding education is crucial for the successful integration of strategies aimed at improving breastfeeding practices and increasing breastfeeding coverage. Additionally, the BFC has potential for broader use, including by other health professionals and as an educational resource in health training programs.